Gaming Disorder and Effects of Gaming on Health: An Overview - Israel Oluwasegun Ayenigbara (Journal of Addiction Medicine and Therapeutic Science - Peertechz Publications, 2018)
Introduction: A video game is any software program that can be played on a computing device, such as a personal computer, gaming console or mobile phone. Video games are age and gender friendly, very popular but like other pleasurable endeavors, can have adverse consequences, which are reviewed.  Aims: This review focuses on the effects of gaming on health, compares gaming with other disorders and opens further discussion on gaming disorder. The overall goal is to explore gaming disorder prevention methods including education, intra- and interpersonal counseling, the role of family and lifestyle modification. Methods: A literature review was performed in Web of Science, Google and Spring Link databases as well as World Health Organization (WHO) material on gaming disorder. Date of publication was not an exclusionary factor but language was a factor. Only English language documents were included in our search.  Results: Multiple system physical health disorders were found to be associated with long-term video game activity. The health problems most cited included visual, muscular-skeletal, obesity and epileptic seizures Conclusions: It is concluded that video gaming has many characteristics of other addiction disorders including deleterious physical and mental health consequences. The social and ubiquitous nature of gaming makes it difficult to recognize the signs and symptoms of excess gaming. Recommendations: Based on a review of the literature, it is recommended gamers become more aware of their time engaging in this popular activity. A greater awareness of signs and symptoms of gaming on daily activities, physical and mental health, and social relationships is encouraged. If persistent gamers experience depression or anxiety, it is recommended that they seek medical or behavioral health professionals.